Reducing men’s health drug costs: exploring the impact of the Mark Cuban Cost Plus Drug Company model on Medicare savings - Adam Khan; Karim Kari; Eli Oldham; Jacob Duncan; Matthew Rashid; Matt Vassar (Journal of Men's Health)
In 2022, national health expenditures in the United States were estimated to have grown from 2.7% to 4.3% and increased further in 2023, reaching an estimated $5.2 trillion. Medicare alone, in 2021, accounted for 21% of national health care spending, amounting to $689 billion in total Medicare expenditures. The Mark Cuban Cost Plus Drug Company (MCCPDC) Model offers a solution by providing prescription medications at lower costs. The objective of this study was to assess the effectiveness of the MCCPDC model in reducing men’s health drug costs compared to Medicare Part D. A comprehensive analysis was conducted on the “Men’s Health” drugs available through the MCCPDC. Prices, including dispensing and shipping fees, were collected for the minimum quantity (30 count) and maximum quantity (90 count) from the MCCPDC. Unit costs and total savings were calculated, and unit prices for 30 count and 90 count prescriptions were compared between Medicare and the MCCPDC. Of the 15 medications in our sample, Medicare’s expenditure amounted to $1.8 billion, with the MCCPDC displaying lower prices overall compared to Medicare. Evaluating 30 count prescriptions, 11 of 15 (73.3%) men’s health drugs resulted in total cost savings of $1.1 billion. For 90 count prescriptions, all 15 drugs yielded savings totaling $1.3 billion. Our study findings highlight substantial potential for cost savings if Medicare were to adjust its contracted rates to those currently set by the MCCPDC. We recommend that healthcare providers include the MCCPDC in patient counseling sessions to educate patients about accessing medications at lower prices. Integrating the MCCPDC as a resource can contribute to significant savings and improve medication affordability.